Penerapan Teknologi Quizizz Dalam Meningkatkan Hasil Belajar pada Pembelajaran Al-Qur’an Hadits - Wildan Rahmawan; Meidi Meidi; Aisyah Nur Dalimunthe; Wimra Sahara (An-Nuha, 2022)
This study aims to determine the Application of Quizizz technology in improving learning outcomes of the Qur'an and Hadith at MIS Model Panyabungan with Idgham material. The background of this study departs from the low involvement of students in the evaluation process at the end of conventional learning which tends to be monotonous and lacks interactivity, so a creative innovation and technology tool is needed to support the success of student evaluation to be better. Therefore, game-based learning technology such as Quizizz is expected to create a more enjoyable, competitive learning atmosphere and motivate students to achieve better learning outcomes. The research method used is classroom action research (CAR) and the design used is in accordance with the Kemmis and MC Taggart models in the form of a plural cycle. This cycle has design stages in each round such as planning, action, observation and reflection. Sampling used qualitative and quantitative with statistical formulas. The subjects of this study were 28 students in class IV-A. Data collection techniques were carried out through observation, documentation, interviews and tests. Based on the results of the study, the application of Quizizz technology can improve the learning outcomes of the Qur'an Hadith. This is evidenced by the observation sheets carried out in cycles I and II. The percentage of students who completed the learning outcomes of cycle I was 85.19% and cycle II 98.92%. So this shows that the application of Quizizz technology can improve the learning outcomes of the Qur'an Hadith in MIS Model Panyabungan.